Associations of regional-level perceived stress and depression with health-related quality of life in Korean adults: a multilevel analysis of 2017 Korea Community Health Survey data - Eunsu Kim; Min-Ho Shin; Jung-Ho Yang; Soon-Ki Ahn; Baeg-Ju Na; Hae-Sung Nam (Epidemiology and Health, 2021)
OBJECTIVES We examined the associations of individual and regional-level perceived stress and depression with health-related quality of life (HRQOL) in Korean adults. METHODS We used data from the 2017 Korea Community Health Survey, which included 216,713 adults living within 254 municipal districts. As individual-level independent variables, perceived stress (higher vs. lower) and depression (Patient Health Questionnaire-9 ≥10) were defined. Regional-level age-adjusted rates of perceived stress (%) and depression (%) were created for 254 municipal districts and categorized into quartiles to generate regional levels of stress and depression. HRQOL was defined as the individual-level EuroQol 5-dimensional index×100. A multilevel analysis was performed to identify the relationship between individual or regional-level independent variables and individual HRQOL. RESULTS In the null model, the proportions of individual variation in the HRQOL explained by region were 1.7% and 2.7% for men and women, respectively. When adjusted with all individual-level variables, regional stress and depression, as well as individual-level perceived stress and depression, were significantly related to HRQOL for both genders. In the full model including all variables, the decrease in HRQOL from the first to the fourth quartile group of regional stress was greater in women (-1.09; 95% confidence interval [CI], -1.87 to -0.31) than in men (-0.65; 95% CI, -1.04 to -0.26). CONCLUSIONS Our results suggest that regional-level perceived stress and depression, as well as individual-level perceived stress and depression, are inversely associated with individual HRQOL.